Volume Decorrelation Effects in TanDEM-X Interferometric SAR Data - Martone, Michele; Rizzoli, Paola; Krieger, Gerhard (IEEE Geoscience and Remote Sensing Letters, 2016)
Among the several factors which may affect the quality of interferometric SAR products, volume decorrelation represents the coherence loss contribution due to the presence of multiple scatterers within a single resolution cell, which results in an increase of the interferometric phase uncertainty. In this letter we investigate the effects of volume decorrelation on X-band TanDEM-X interferometric data. TanDEM-X is the first bistatic space-borne SAR mission and provides a unique, global, and manifold interferometric data set to be exploited for a variety of scientific and commercial applications. The main goal of this paper is to provide the scientific community with a characterization of volume decorrelation effects occurring at X-band for different land cover types and acquisition geometries. The potentials of volume decorrelation contribution at X-band for land classification are discussed as well and some application examples are presented.
DLR Import::2019-04-02
Keywords: Classification; SAR interferometry (InSAR); synthetic aperture radar (SAR); TanDEM-X mission; volume decorrelation